Peningkatan Kemampuan Siswa Sekolah Menganalisis Arti, Makna dan Melafalkan Al-Asmaul Al-Husna melalui Media Audio-Visual - Rustam Samsi Hidayat; Mus Mulyadi (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Learning outcomes in Islamic Religious Education, particularly in understanding and reciting al-Asmaul al-Husna, are often constrained by conventional teaching methods that emphasise memorisation and provide limited opportunities for student engagement. Objective: This study aimed to examine improvements in students’ ability to analyse the meaning and correctly recite al-Asmaul al-Husna through the application of audiovisual media in Islamic Religious Education. Method: The study employed a classroom action research design conducted at SDN 36 Bengkulu Selatan in 2023. The participants consisted of 24 fourth-grade students. Data were collected through classroom observations and achievement tests, while data analysis was conducted by comparing students’ learning outcomes with the Minimum Completeness Criteria (KKM) across learning cycles. Findings: The findings revealed a consistent increase in students’ learning outcomes across three learning cycles. The use of audiovisual media significantly enhanced students’ ability to analyse the meanings of al-Asmaul al-Husna and accurately recite it, as well as their engagement during the learning process. Conclusion: The integration of audiovisual media proved effective in improving learning outcomes in Islamic Religious Education, particularly by enhancing students’ conceptual understanding and accuracy in reciting al-Asmaul al-Husna. Contribution: This study offers practical insights for teachers and prospective educators by demonstrating that engaging, technology-based audiovisual media can foster active learning, increase student motivation, and strengthen students’ understanding of Islamic religious concepts.